The Impact of Restrictions on the State-Owned Enterprises to Expand their Operations into New Product Lines in Latvia - Vircavs, Inguss (Vilnius University Proceedings, 2024)
There is a practice among OECD countries of establishing restrictions for state-owned enterprises to develop new products in addition to their main production. Scarce attention is paid to how such an approach affects public enterprises’ performance in favour of the public good; thus, it must be clarified. This research aims to propose competition policy improvements based on the evaluated impact of new product restrictions on competition neutrality. The research methodology includes interviews with Latvian public sector stakeholders concerning the advantages of optimal use of the company’s resources and risks’ diversification. Private sector disadvantages if state-owned enterprises offer their products in private-dominated markets are considered. It was observed that national policy is contradictory: there is an emphasis on efficiency goals, but the expansion initiatives by state-owned enterprises in the market are accepted reluctantly. Taking advantage of state-owned enterprises to boost R&D innovations is important to fostering Latvian regional development policies.